Anatomical approach of learning Anatomy - perspective of medical students on Traditional versus Virtual methods - Sharma, Ankur; Bansal, Archisha; Gupta, Nirupma; Bansal, Gaurav; Bansal, Shweta; Goel, Uday (Journal of Neonatal Surgery, 2025)
Introduction: Anatomy education is essential in medical training, traditionally relying on cadaveric dissection for comprehensive learning. Cadaveric dissection not only enhances students' anatomical knowledge but also promotes teamwork, professional skills, and ethical understanding. With advancements in technology, virtual dissection methods such as VR, AR, and 3D modeling are emerging as supplementary tools, potentially enhancing accessibility and reducing psychological strain. Aims and Objectives: This study aims to examine medical students' perceptions of various anatomy education methods, including cadaveric dissection versus virtual dissection, in understanding the complexities of human anatomy. It also seeks to evaluate their confidence levels and skill development associated with each method. Additionally, the study assesses the effectiveness of these approaches and explores the potential integration of a hybrid model in contemporary anatomy education. Materials and Methods: This study surveyed 262 undergraduate medical students at 8 medical colleges in Delhi National Capital Region (NCR), examining their preferences and perceptions regarding cadaveric learning and virtual learning. A structured questionnaire assessed students' experiences and confidence in anatomy learning through these methods. A cross-sectional study design was used, gathering data through a validated, anonymous Google Forms questionnaire. The questionnaire included Likert scale questions—used to measure levels of agreement or confidence—and additional multiple-choice and open-ended questions, analyzing demographic factors, educational preferences, and perceived confidence levels with each method. Results: Most students (57.6%) regarded cadaveric dissection as essential in the curriculum and 30.9% supported hybrid approaches combining traditional and virtual methods. Students preferred cadaveric dissection for skill-building and confidence in clinical practice but virtual tools were valued highly for review and accessibility. Only 11.5% favored prosection exclusively. Conclusion: Cadaveric dissection remains indispensable for developing practical skills, though hybrid approach utilizing both traditional and virtual methods is widely preferred and it offers a balanced, comprehensive anatomy education model. Institutions should integrate these methods to optimize clinical preparedness and professional competence in medical students.